Genotype x environment effects on cassava response to the green mite (Mononychellus tanajoa) - Nukenine, E.; Dixon, A.; Ngeve, J. (2002)
Genotype x environment (G x E) interactions frequently complicate breeding efforts and delay progress in selection. The cassava green spider mite (CGM) (Mononychellus tanajoa Bondar) is a serious constraint to Cassava production in Africa. Nine cassava genotypes were grown at 6 representative locations for 3 years to study G x E interaction patterns for tile reaction of cassava genotypes to CGM, and to identify genotypes with stability to the pest, using the Additive Main Effects and Multiplicative Interaction (AMMI) statistical model Environments, genotypes and G x E interactions were highly significant (P < 0.01) for the pest. The G x E interactions accounted for 24.7%, of the treatment sum of squares for CGM